Pengaruh Variasi Kosentrasi Tepung Tapioka Termodifikasi Dengan Metode Enzimatis Sebagai Bahan Substitusi Pada Proses Pembuatan Mie - Putri, Itci Amada; Abdillah, Hamid (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Indonesia has dependency to rice Enough high , so request rice very tall And when happen scarcity rice inside _ country . So needed innovation product For cope problem such , ie Wrong only one replace rice with noodles wet as alternative  replacement source carbohydrates . Material raw making noodles wet on study This is flour tapioca modified And flour wheat as material substitution . Expected with use material non- flour basis For product noodles capable replace dependency use flour flour . On study This use variation comparison composition flour tapioca modified And flour different flour _ namely ; (10%:90%, 25 % : 75%, and 30%:70%) use variation concentration enzyme 10%, 20%, 30%, 40%, and 0% as control parameters . Results study show comparison flour tapioca modified influential to noodle water content wet And quality noodles wet include (aroma, elasticity , and color ). Highest water content that is sample noodles wet on ratio of 30% flour tapioca modified and 70% flour wheat with 40% enzyme concentration of 64.54 % . According to Body Standard Indonesian National requirements quality noodle water content good wet is 65%, got concluded that noodles wet fulfil requirements.